From viruses to oncolytics - Cattaneo, Roberto (Henry Stewart Talks, 2007)
Viruses: molecular biology and reverse genetics, Tropism determinants: entry and post-entry levels, Tropism targeting: protease activation, receptor attachment, transcription/replication, spread, Cancer clinical trials: recombinant adeno-, herpes, vaccinia and measles viruses
Archived at 2018/02/28